Pamphlet of games for the preparation of the family in the stimulation to the development of the pre-writing - Haydee Herrera-Terry; Nordis Sánchez-Quintero (Universidad de Guantánamo, 2013)
The constant and differentiated preparation of the family constitutes one of the most important goals in the Pre-school Education, in this sense the principle referred to the protagonist participation of the family and the community in the educational process, together to the inter-sector focus, constitute essential characteristics of the success of the integral education of children from 0 to 6 years. The work evaluates the inadequacies detected in the preparation of the family for the stimulation to the development of pre- writing in children through movement games which has rebounded unfavourably in the diagnostic of the Pre-school graduate. The practical contribution consists on a methodological instrument based on a Pamphlet of movement Games to eradicate some lacks of learning taking advantage of the potentialities of the inter-discipline relations.